ETIOPATHOGENETIC FEATURES OF VOCAL FOLD NODULES IN CHILDREN AGAINST THE BACKGROUND OF CHRONIC PHARYNGEAL DISEASES - Aadil Ramdin (International Journal of Literature and Language Studies, 2024)
Vocal fold nodules (VFN) represent the primary organic cause of pediatric dysphonia, traditionally attributed to chronic mechanical phonotrauma. However, recent clinical evidence suggests that the pediatric larynx does not exist in isolation; its health is inextricably linked to the upper aerodigestive tract. This thesis explores the complex etiopathogenetic synergy between VFN and chronic pharyngeal diseases, such as chronic tonsillitis and pharyngitis. It posits that chronic pharyngeal inflammation serves as a "pro-inflammatory substrate" that lowers the threshold for mechanical injury, stabilizes the presence of nodules, and prevents spontaneous regression. By synthesizing statistical data, acoustic analysis, and histological markers, this work argues for a holistic diagnostic paradigm in pediatric laryngology.